2020
DOI: 10.1063/1.5124821
|View full text |Cite
|
Sign up to set email alerts
|

Effects of medium range order on propagon thermal conductivity in amorphous silicon

Abstract: We discuss the dependence of the propagon contribution to thermal conductivity on the medium range order (MRO) in amorphous silicon. Three different amorphous structures with the same size of 3.28 nm were studied. Among these three structures, two structures were constructed with experimentally observed MRO [Treacy and Borisenko, Science. 335, 6071 (2012)] and the other structure is from continuous random network (CRN), which lacks MRO and thus represents a randomized amorphous structure [Barkema and Mousseau,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Among them, the low-frequency propagons, resembling phonons in crystalline solids, have relatively large mean free paths and high heat transfer efficiency 52 . Previous theoretical simulation results have shown that an amorphous material with higher MRO exhibits larger thermal conductivity as the propagon thermal conductivity in a MRO structure is larger than that in an ideal amorphous structure 13 . This is the reason why the current sp 3 amorphous carbon with higher local structural order exhibits such a high thermal conductivity.…”
Section: Discussionmentioning
confidence: 94%
“…Among them, the low-frequency propagons, resembling phonons in crystalline solids, have relatively large mean free paths and high heat transfer efficiency 52 . Previous theoretical simulation results have shown that an amorphous material with higher MRO exhibits larger thermal conductivity as the propagon thermal conductivity in a MRO structure is larger than that in an ideal amorphous structure 13 . This is the reason why the current sp 3 amorphous carbon with higher local structural order exhibits such a high thermal conductivity.…”
Section: Discussionmentioning
confidence: 94%
“…With these three widely used normal mode methods reviewed, we reiterate here what the normal mode methods predict of thermal transport in amorphous silicon [12,[17][18][19][20][21].…”
Section: Allen and Feldman Theorymentioning
confidence: 99%
“…The literature on normal mode descriptions of a-Si has some variations in detailed conclusions, but the general consensus is that propagons contribute from 20 to 50 % of overall thermal conductivity despite their small population consisting of only ∼ 3 % of the density of states [8,12,[17][18][19][20][21], and that they are dominantly scattered by anharmonicity [12,17,18].…”
Section: Introductionmentioning
confidence: 99%